Training teachers of science for the new society - Hernandez, Dolores Fuentes (Education quarterly.)
Upgrading science teaching must be done as a cooperative effort of almost all sectors engaged in teacher education. Science teaching centers fulfill a much-needed role as initiators of innovations, as sources of improved curricula, improved methodology of teaching but if the other departments in colleges of education or teacher-training institutions which are concerned with teacher education are not involved, the s cience teaching improvement program may not be as effective nor as efficient as it might otherwise be. An overall view of the program of the SEPP involves various institutions and agencies.